Effect of 35% sodium ascorbate combined with 0.4% surfactant on resin tag length in composite restorations following intracoronal bleaching - Arlini, Rakhmalita; Nugraheni, Tunjung; Mulyawati, Ema (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
The application of 35% hydrogen peroxide in intracoronal bleaching generates free radicals that shorten resin tags and weaken the bond strength of composite resin restorations. Although 35% sodium ascorbate can neutralize free radical residues, its molecular instability limits its effectiveness. The addition of surfactants may enhance both the penetration ability and stability of sodium ascorbate. This study aimed to investigate the effect of adding 0.4% surfactant to 35% sodium ascorbate on the length of resin tags in composite resin restorations following intracoronal bleaching. Thirty mandibular premolars were prepared with standardized Class I cavities measuring 2.7 mm in diameter and 6 mm in depth. A 35% hydrogen peroxide gel was applied to the cavities for five consecutive days. After bleaching, the samples were randomly assigned to three groups of ten teeth each. The first group was stored in an incubator for seven days before undergoing composite resin restoration. The second group received an application of 35% sodium ascorbate, which was then rinsed off before immediate composite restoration. The third group received an application of 35% sodium ascorbate combined with 0.4% surfactant, followed by rinsing and immediate composite restoration. Histological preparations were made using hematoxylin-eosin staining and observed under a light microscope at 400× magnification. Resin tag lengths were measured using the Image Raster application. The one-way ANOVA test revealed a statistically significant difference among the groups (p = 0.000). Post-hoc LSD analysis showed that resin tag lengths in the third group were significantly greater than those in both the first and second groups (p = 0.000 for both comparisons). These results indicate that the combination of 35% sodium ascorbate with 0.4% surfactant significantly increases resin tag length and may enhance the bonding performance of composite restorations following intracoronal bleaching.